2013
DOI: 10.1016/j.cub.2013.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Halotropism Is a Response of Plant Roots to Avoid a Saline Environment

Abstract: Tropisms represent fascinating examples of how plants respond to environmental signals by adapting their growth and development. Here, a novel tropism is reported, halotropism, allowing plant seedlings to reduce their exposure to salinity by circumventing a saline environment. In response to a salt gradient, Arabidopsis, tomato, and sorghum roots were found to actively prioritize growth away from salinity above following the gravity axis. Directionality of this response is established by an active redistributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
292
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(338 citation statements)
references
References 38 publications
27
292
1
Order By: Relevance
“…Such enhanced uptake is postulated to be partially due to the induction of a sterol-sensitive (lipid raft-dependent) pathway, which is not responsible for the uptake of aquaporins under control conditions. In addition, the salt-induced upregulation of PIN2-GFP uptake in epidermal cells in the presence of inhibitors that abolish clathrin recruitment to the PM has been described (Galvan-Ampudia et al, 2013). Our data support these previous and contemporary findings.…”
Section: Discussionsupporting
confidence: 92%
“…Such enhanced uptake is postulated to be partially due to the induction of a sterol-sensitive (lipid raft-dependent) pathway, which is not responsible for the uptake of aquaporins under control conditions. In addition, the salt-induced upregulation of PIN2-GFP uptake in epidermal cells in the presence of inhibitors that abolish clathrin recruitment to the PM has been described (Galvan-Ampudia et al, 2013). Our data support these previous and contemporary findings.…”
Section: Discussionsupporting
confidence: 92%
“…The link between genes involved in growth and development and their expression in pollen and root tissue seems reasonable, considering that the pollen tube represents a prime example of directional cellular growth (Cheung and Wu, 2008) and that the root tip is also involved in directional responses to developmental and environmental cues (Abas et al, 2006;Galvan-Ampudia et al, 2013). Maybe less clear is the link between genes involved in defense and their expression in aerial tissues, especially since the expression compendium we used does not contain any stress conditions.…”
Section: Functional Divergence Of Homoeologs and Their Respective Coementioning
confidence: 99%
“…For other genes, indicated in light gray, no relation to any of these processes could be found in literature. References to relevant literature are in Supplemental Data Set 1. role in the regulation of cell expansion in pollen tubes (Pleskot et al, 2013) and in root tropism (Galvan-Ampudia et al, 2013) (Figure 4). Interestingly, PA directly interacts with the actin cytoskeleton and as such influences vesicular trafficking to the cellular site of PA signaling (Pleskot et al, 2013;Hong et al, 2016).…”
Section: Homoeologous Gene Pairs Show Associated Functions In Cell Wamentioning
confidence: 99%
“…Likewise, jasmonate, another plant hormone, has been demonstrated to regulate PIN2 endocytosis, although a connection with CME has not been established (Sun et al, 2011). Recently, common salt was identified as another trigger for PIN2 CME in root meristem cells, and it was suggested that it causes auxin redistribution resulting in root growth in a direction away from harmful salt concentrations (Galvan-Ampudia et al, 2013). Auxin, by contrast, inhibits the CME of several plasma membrane-resident proteins including PIN1, PIN2, PIN4, PIP2 and PMA (Paciorek et al, 2005).…”
Section: Developmental and Environmental Control Of Cargo Internalizamentioning
confidence: 99%